Governança de tecnologia de informação: estrutura e práticas - Albertin, Rosa Maria de Moura (2008)
Information Technology (IT) plays a leading role in organizations given its importance and how dependent every business process is on this technology. In this context, the need arises to address certain aspects of IT management, such as governance, which deals with IT not only internally, but with the active involvement of the business area. Information Technology Governance (ITG) is responsible for maintaining the connection between IT and the organization, by means of an alignment process that creates results consistent with organizational requirements, as well as through a Strategic IT decision-making process. In this paper, ITG was analyzed within a broad and strictly strategic context, as an element of IT management as concerns supporting the organization with specific solutions appropriate to organizational needs and as part of corporate governance, as a means to stay in line with organizational objectives and incorporate practices and policies into its action plan. This study aimed to establish a definition for ITG, the main aspects, factors and practices that make up an ITG structure. The selected research method was case study, where we attempted to provide an in-depth analysis of the implementation of an ITG model. As a result, the ITG structure enables aligning business vision with IT capabilities through the definitions of context, cope, application and participants. The observed practices allow dealing with factors and how they can be obtained, as well as noting how the organization treats ITG based on an implementation and evaluating script. The ITG structure needs to take account of the IT role and the organization's specific needs. Adoption of such a structure may improve how IT is treated and how it must be structured to meet organizational objectives and lead to positive impacts performance.